Tissue engineering and regenerative medicine - Pham, Phuc Van (Advances in experimental medicine and biology, 2019)
1. Physico-mechanical properties of HA/TCP pellets and their three-dimensional biological evaluation in vitro -- 2. The robust potential of mesenchymal stem cell-loaded constructs for hard tissue regeneration after cancer removal -- 3. In vitro production of cartilage tissue from rabbit bone marrow derived mesenchymal stem cells and polycaprolactone scaffold -- 4. Stem Cell Therapy for Tendon Regeneration: Current Status and Future Directions -- 5. Stem cells therapy and type 1 diabetes mellitus: Treatment strategies and future perspectives -- 6. Characterization of senescence of human adipose-derived stem cells after long-term expansion -- 7. Sports injuries: Diagnosis, Prevention, Stem cells therapy and medical Sport strategy -- 8. Stem cell therapy for multiple sclerosis -- 9. Stem Cells from Human Extracted Deciduous Teeth Expanded in Foetal Bovine and Human Sera Express Different Paracrine Factors after Exposure to Freshly Prepared Human Serum -- 10. Molecular mechanisms responsible for anti-inflammatory and immunosuppressive effects of mesenchymal stem cell-derived factors -- 11. Evaluation of proliferation and osteogenic differentiation of human umbilical cord derived mesenchymal stem cells in porous scaffolds